PERBANDINGAN INTERPRETASI SKALA NYERI ANTARA NRS-VAS-WBFS OLEH PASIEN PASCA OPERASI ELEKTIF ORTHOPEDI DI RSUD Dr. SOETOMO - Pratitdya, Ginong; Rehatta, Nancy M.; Susila, Dedi (Universitas Tribhuwana Tunggadewi, 2020)
Health management is still a challenge in health services. An instrument that can cure pain is easy, easy, with accurate interpretation and can be used by every party involved in pain management. The purpose of this study was to analyze the Numeric Rating Scale (NRS), Visual Analogue Scale (VAS), and Wong Baker Faces Scale (WBFS), which can be interpreted well by postoperative care patients. The research method used was an observational analytic study with a cross-sectional study design that analyzed the scale application (NRS, VAS, WBFS) in patients after elective orthopedic surgery at RSUD Dr. Soetomo Surabaya. This study analyzed primary data of postoperative patients which contained socio-demographic characteristics, type of anesthesia given, pain scores and patient interpretation of pain scales through special instruments. The results showed that 102 research subjects were needed. The pain scale interpretation instrument was declared valid and reliable (Cronbach Alpha> 0.60). Mean pain scores from the VAS scale (4.29), NRS (4.82) and WBFS (4.81). No significant difference was obtained NRS scale and WBFS scale (Sig> 0.05). Mean interpretation of pain scale from the VAS scale (13.62), NRS (17.14) and WBFS (21.33). There was a significant difference in the pain score of the VAS scale against the NRS scale, also the WBFS scale (Sig